Flower‐Like Nanozymes with Large Accessibility of Single Atom Catalysis Sites for ROS Generation Boosted Tumor Therapy. (31st December 2021) - Xing, Yuxin; Wang, Lu; Wang, Liucan; Huang, Jixi; Wang, Shuai; Xie, Xiyue; Zhu, Jing; Ding, Tao; Cai, Kaiyong; Zhang, Jixi
Abstract: The use of reactive oxygen species (ROS) generators based on single‐atom catalysts (SACs) has been an emerging strategy for mediating tumor therapy, however, the current systems suffer from low mass transport efficiency. Here, a novel strategy of morphology fragmentation is developed to fabricate flower‐like SAC nanozymes with greatly improved 3D accessibility of active sites. Specifically, the coordinationally polymerized zeolite imidazole framework acts as a polyphenol oxidase‐like enzyme to catalyze the in situ polymerization of polydopamine (PDA) which leads to blockage of micropores and crosslinking of the morphology‐deteriorated ZIF nanosheets. The protective carbonization by PDA results in SAC nanozymes (C‐NFs) with plenty of reopened micropores and defect mesopores (≈4 nm) in the nanopetals, large interpetal pore space (≈39 nm), high surface area (388 m 2 g −1 ), as well as an ultrahigh loading metal atoms (27.3 wt%). Subsequently, a superior peroxidases‐like activity (36.6‐fold increment in the turnover frequency) facilitates significantly strengthened ROS generation and damage of biomolecules. Moreover, the employment of apoferritin modification/loading leads to particle dispersion in solution and concomitant drug loading. The following cancer cell re‐sensitization is proven to be advantageous for boosting ROS‐facilitated treatment of drug‐resistant tumors, opening up new avenues for ROS therapy. Abstract : Flower‐like single‐atom catalyst nanozymes are prepared by a "polymer‐assisted morphology fragmentation" mechanism to boost reactive oxygen species generation in tumor microenvironments. The unique morphology not only allows for accessibility of the catalytic sites within the structure, substrate diffusion, and reaction kinetics, but also provides a platform for oxidative stress‐induced sensitization and treatment of therapy‐resistant tumors.